Search for CP violation in Ξ−b → pK−K− decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review, 2021)
A search for CP violation in charmless three-body Ξ−b→pK−K− decays is performed using pp collision data recorded with the LHCb detector, corresponding to integrated luminosities of 1 fb−1 at a center-of-mass energy √s=7 TeV, 2 fb−1 at √s=8 TeV and 2 fb−1 at √s=13 TeV. A good description of the phase-space distribution is obtained with an amplitude model containing contributions from Σ(1385), Λ(1405), Λ(1520), Λ(1670), Σ(1775) and Σ(1915) resonances. The model allows for CP -violation effects, which are found to be consistent with zero. The branching fractions of Ξ−b→Σ(1385)K−, Ξ−b→Λ(1405)K−, Ξ−b→Λ(1520)K−, Ξ−b→Λ(1670)K−, Ξ−b→Σ(1775)K− and Ξ−b→Σ(1915)K− decays are also reported. In addition, an upper limit is placed on the product of ratios of Ω−b and Ξ−b fragmentation fractions and the Ω−b→pK−K− and Ξ−b→pK−K− branching fractions.
Im Titel ist "-" hochgestellt und "b" tiefgestellt
LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, N. Meinert, A.B. Morris, S. Neubert, M. Sarpis, M. Schmelling, D.J. Unverzagt, U. Uwer, H. Viemann, R. Waldi, C. Wang, L. Witola, M. Zavertyaev, A. Zhelezov, und weitere 937
Gesehen am 12.11.2021